Importance of geological information for assessing drain flow in a Danish till landscape. Issue 3 (17th December 2018) - Hansen, Anne Lausten; Storgaard, Anne; He, Xin; Højberg, Anker Lajer; Refsgaard, Jens Christian; Iversen, Bo Vangsø; Kjaergaard, Charlotte
Abstract: There has, in recent years, been an increasing interest in developing nutrient load mitigation measures focussing on tile drains. To plan the location of such tile drain measures, it is important to know where in the landscape drain flow is generated and to understand the key factors governing drain flow dynamics. In the present study, we test two approaches to assess spatial patterns in drain flow generation and thereby assess the importance of including geological information. The approaches are the widely used topographical wetness index (TWI), based solely on elevation data, and hydrological models that include the subsurface geology. We set‐up an ensemble of 20 hydrological models based on 20 stochastically generated geological models to predict drain flow dynamics in the clay till Norsminde catchment in Denmark and test the results against TWI. We find that the hydrological models predict observed daily drain flow reasonably well. High drain flow volumes were found in stream valleys and in wetlands and lower drain flow volumes in the more hilly parts of the catchment. In spite of the apparent connection to the landscape, there was no statistically significant correlation between TWI and drain flow at grid scale (100 × 100 m). TWI was therefore not found to be a sufficient index on its own to assess where drain flow is generated, especially in the highlands of the catchment. The geology below 3 m was found to have a large impact on the drain flow, and correlations between sand percentage in the subsurface geology and drain flow volume were found to be statistically significant. Geological uncertainty therefore give rise to uncertainty on simulated drain flow, and this uncertainty was found to be high at the model grid scale but decreasing with increasing scale.